The influence of perception of in-store colour on consumers' in-store behaviour - Osman, Syuhaily; Othman, Md Nor (Malaysian Consumer and Family Economics Association, 2009)
The primary objective of this study is to examine the influence of perception of in-store colour on consumers' in-store behaviour. Using a mall intercept technique, which used a self-administered questionnaire, a survey of shoppers in clothing and apparel stores at selected shopping centre's was carried out. The result of structural equation modeling found that in-store colour has significantly influenced mood, which in turn, mood was found to significantly affect respondents' time spent, money spent, and repatronage intention. The perception of in-store colour was also found to directly influence the consumers' in-store behaviour. This study would give some useful information to marketing managers and retailers with regards to the importance of in-store colour to attract more shoppers to patronise their stores, with comfortable, yet exciting and satisfying experiences.